THE ROLE OF JUDICIAL ADMINISTRATION OF THE GOVERNMENT ACTION ARBITRARY OR VIOLATE RIGHTS CITIZENS - Syaprillah, Aditia (Tadulako Law Review, 2017)
The state of judicial administration is formed in order to provide protection for justice seekers who felt indiscriminate with the decision made by judicial administration. Government policies have released with careful consideration on the interest of citizen, therefore district institutions have to be set up as a means for control system.Goal of this study is to analyze the role of state judicial administration to provide protection from indiscrimination for all citizens. The research methods used in this study are normative and doctrine approaches, which are statute approach and regulation approach. Government authority has taken by regulation cannot be operated freely.